Archives and/as battlefields: Political aspects of historiographic revision. (June 2019) - Barak, On
For a short window of time between the deposition of Hosni Mubarak and the resumption of authoritarianism, Egyptian archives have become turbulent arenas in the struggle for governmental transparency and for democratic politics. This essay examines how attempting to access historical records pertaining to the Arab-Israeli 1973 war—arguably the most significant event reinforcing the reign of the Free Officers and their acolytes and a moment that encapsulates for many Egyptians "history" in a broader sense—became an important frontier in this struggle. After the war, various arenas in Egypt became lieus of war commemoration: not milieus that allowed a meaningful and agentive engagement with history, but sites that affixed a rigid, impoverished, and impoverishing understanding thereof. In postbellum Egypt, and much more so after 2011, contention revolved around transforming such sites into more open-ended environments.